2014
DOI: 10.1115/1.4026983
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Injection and Cavity Pressure on the Demoulding Force in Micro-Injection Moulding

Abstract: The paper reports an experimental study that investigates part demoulding behavior in micro-injection moulding with a focus on the effects of pressure and temperature on the demoulding forces. In particular, the demoulding performance of a representative microfiuidics part was studied as a function of four process parameters, melt temperature, mould temperature, holding pressure, and injection speed, employing the design of experiment approach. In addition, the results obtained using different combinations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Consequently, to achieve a complete and preferable replication, a combination of different processing parameters is necessary. A design of experiments (DoE) method has been used in a number of studies 18,20,28,86,88 . Through a DoE method, experimental data is acquired in a controlled way; the significant and non-significant factors affecting a process are determined, and, finally, the behavior of injection molding of micro-nanostructures can be carefully monitored.…”
Section: Processing Parametersmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, to achieve a complete and preferable replication, a combination of different processing parameters is necessary. A design of experiments (DoE) method has been used in a number of studies 18,20,28,86,88 . Through a DoE method, experimental data is acquired in a controlled way; the significant and non-significant factors affecting a process are determined, and, finally, the behavior of injection molding of micro-nanostructures can be carefully monitored.…”
Section: Processing Parametersmentioning
confidence: 99%
“…No matter how high the mold and melt temperatures are, a great pressure is needed to push the molten material into the structures. In addition to the role of holding pressure in pushing the polymer into the holes, it also could compensate for the trapped air pressure and polymer shrinkage 28,53 . It has been reported that pressure over 150 MPa is an appropriate holding pressure for a complete filling of micro-nanostructures, however too many processes work with lower pressures 53 .…”
Section: Holding Pressurementioning
confidence: 99%
See 2 more Smart Citations
“…However, a coating with a lower level of surface friction than typical metals used for moulds, such as steel, can be added to the mould to decrease the ejection stress [5]. Griffiths et al [6] report how to monitor such forces during ejection of microsized parts as it is considered such an important factor but is not of high concern during conventional injection moulding. De Santis et al [7] developed a system whereby the mould surface temperature could be increased by some tenths of a Celsius degrees in a matter of a second.…”
Section: Introduction*mentioning
confidence: 99%